Optimal performance of voltage-probe quantum heat engines - Sartipi, Zahra; Vahedi, Javad (Physical review, 2023)
The thermoelectric performance at a given output power of a voltage-probe heat engine, exposed to an external magnetic field, is investigated in linear irreversible thermodynamics. For the model, asymmetric parameter, general figures of merit, and efficiency at a given output power are analytically derived. Results show a tradeoff between efficiency and output power, and we recognize optimum-efficiency values at a given output power are enhanced compared to a Büttiker-probe heat engine due to the presence of a characteristic parameter, namely, dm. Moreover, similar to a Büttiker-probe heat engine, the universal bounds on the efficiency are obtained, and the efficiency at a given output power can exceed the Curzon-Ahlborn limit. These findings have practical implications for the optimization of realistic heat engines and refrigerators. By controlling the values of the asymmetric parameter, the figures of merit, and dm, it may be possible to design more efficient and powerful thermoelectric devices.